A Comparative Analysis of the Chloroplast Genomes of Four Polygonum Medicinal Plants - Guo, Shuai; Liao, Xuejiao; Chen, Shiyu; Liao, Baosheng; Guo, Yiming; Cheng, Ruiyang; Xiao, Shuiming; Hu, Haoyu; Chen, Jun; Pei, Jin; Chen, Yangjin; Xu, Jiang; et al. (Frontiers in Genetics, 2022)
Polygonum is a generalized genus of the Polygonaceae family that includes various herbaceous plants. In order to provide aid in understanding the evolutionary and phylogenetic relationship in Polygonum at chloroplast (cp) genome-scale level, we sequenced and annotated the complete chloroplast genomes of four Polygonum species using next-generation sequencing technology and CpGAVAS. Then, repeat sequences, IR contraction, and expansion and transformation sites of chloroplast genomes of four Polygonum were studied, and a phylogenetic tree was built through chloroplast genomes of Polygonum. The results indicated that the chloroplast genome construction of Polygonum also displayed characteristic four types of results, comparable to the published chloroplast genome of recorded angiosperms. The chloroplast genomes of 4 Polygonum plants are highly consistent in genome size (159,015 bp-163,461 bp), number of genes (112 genes, including 78 protein-coding genes, 30 tRNA genes, 4 rRNA genes), gene types, gene order, the codon usage and repeat sequence distribution, which identifies the high preservation among Polygonum chloroplast genomes. The Polygonum phylogenetic tree was recreated by full sequence of the chloroplast genome, which illustrates that the P. bistorta, P. orientale and P. perfoliatum are divided into the same branch, and P. aviculare belongs to Fallopia. The precise system site of lots base parts still requires further verification, but study would provide a basis for developing the available genetic resources and evolutionary relationships of Polygonum.